EXPLORING SECONDARY STUDENTS' ENGAGEMENT OF THE COLLABORATIVE WRITING APPROACH TO LEARNING IN WRITING DESCRIPTIVE TEXT - Geana Sekar Maharani; Iwan Ridwan; Yogi Setia Samsi (PROJECT (Professional Journal of English Education), 2023)
Student engagement encourages the advancement of writing skills, such as the ability to compose descriptive language. The evaluated students' writing abilities are determined by their behavioral, emotional, and cognitive engagement. However, the purpose of this study is to investigate and learn about the utilization of collaborative writing styles when completing descriptive writing. This study used the descriptive qualitative method and engaged six students in writing descriptive text in the group. The data was gathered through semi-structured interviews. To fill a gap in the research on student engagement in collaborative writing approaches. The findings show how collaborative writing approaches improve student involvement and help students overcome problems when producing descriptive writing. Furthermore, collaborative writing enhanced students' enthusiasm for creating descriptive texts as well as their ability to communicate with other students. As a result, students regard the complicated process of collaborative writing as challenging. Students' behavioral, affective, emotional, and cognitive skills are all enhanced as a result of collaborative writing. The other researcher discovered low affective engagement as a result of students' uncertainty regarding collaborative writing during the writing process of descriptive texts.